Interleukin 6, Ferritin Levels, and Glasgow Prognostic Score in Solid Cancer - Rotty, Linda; Padang, Mersy; Hendratta, Cecilia; Haroen, Harlinda; Lasut, Pearla (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Several pro-inflammatory cytokines have been shown to regulate cancer cell growth and contribute to cancer promotion and progression. Interleukin 6 (IL-6) regulates almost all the hallmarks of cancer such as inhibition of apoptosis, proliferation, angiogenesis, and invasiveness and is also known to regulate cell metabolism. The associated increase in serum ferritin is most likely induced by the inflammatory state. In several studies, IL-6 and ferritin have a significant role in the development and clinical outcome in solid cancer and the Glasgow Prognostic Score (GPS) is widely used as a prognostic score in solid cancer. It is currently unclear whether levels of IL-6 and ferritin correlate with GPS in solid cancer patients. AIM: The aim of this study is to determine the correlation between IL-6 and ferritin levels with the GPS in solid cancer patients. METHODS: This study was an analytical observational study with a cross-sectional study approach to examine the relationship between IL-6 and ferritin levels with GPS in solid cancer patients. The sampling method was carried out by consecutive sampling. The total number of samples used in the study was 32 solid cancer subjects who had just been diagnosed. IL-6 was examined by kit enzyme-linked immunosorbent assay and ferritin using immunochemiluminescent method at certified laboratory in Manado city, Indonesia. The GPS is based on the results of the patient’s C-reactive protein and albumin levels were also examined at certified laboratory in Manado city, Indonesia. Data analysis was done using SPSS version 22. RESULTS: There were 32 patients with solid cancer who are newly diagnosed and have not undergone chemotherapy. Out of 32 patients, 17 are men (53.13%) and 15 are women (46.87%). The median age of the subject was 52.5 (33–69) years. There was a significant relationship between IL-6 levels and GPS (p = 0.011; OR 16.67 95% CI 1.617–171.783). There was no significant relationship between ferritin levels and GPS (p = 0.148; OR 5.429 95% CI 0.807–36.506). There was a statistically significant relationship between IL-6 levels and ferritin (r = 0.554; p = 0.001). CONCLUSION: There was a significant correlation between IL-6 and GPS and there was a significant correlation between IL-6 and ferritin in solid cancer patients. IL-6 levels can be used to assess the risk of prognosis in solid cancer patients and help provide an idea of what kind of treatment will be given to patients, and can help to determine the plan treatment at the end of the life of cancer patients.